EFEKTIVITAS MODEL PEMBELAJARAN INQUIRY LEARNING DAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN MATEMATIKA KELAS 4 SD GUGUS HASANUDDIN - Dian Ndaru Anjarwati, Indriyana; Astuti, Suhandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to determine the effectiveness of the Problem Based Learning model compared to the Inquiry Learning model in enhancing critical thinking skills in fourth-grade mathematics learning at elementary school. The research method used was Quasi Experimental with a Nonequivalent Control Group design. The population consisted of 199 fourth-grade students at Hasanuddin Elementary School cluster, but only 57 students were selected as the research sample. Data collection techniques included pretest and posttest using essay questions and non-test techniques such as observation sheets of teacher and student activities, as well as rubrics for critical thinking skills. The T-test results showed that the Asymp Sig. (2-tailed) value was 0.000 < 0.05, thus rejecting the H0 and accepting the Ha, indicating that the application of the Problem Based Learning model was significantly superior to the Inquiry Learning model in improving critical thinking skills in fourth-grade mathematics at Gugus Hasanuddin Elementary School cluster. The research also revealed a significant difference in the average test scores between the two experimental groups, where difference in the average pretest and posttest scores of experimental group1 were 17.16, while experimental group 2 was only 7.77. These findings indicate that the PBL model is highly effective compared to the Inquiry Learning model in enhancing critical thinking skills.